Identification of Suitable Reference Genes for Gene Expression Normalization in Jatropha curcas L During Development and Under Stress Conditions Using Real Time Quantitative PCR - Rocha,Antonio José (2016)
Jatropha curcas L represent a potential source of raw material for the production of biodiesel. The aim this study was to find potential candidate reference genes in J. curcas tissues. Three softwares were utilized to verify which would be the most stable reference genes in qPCR assay: GeNorm, NormFinder and BestKeeper. The most stable reference genes in developing J. curcas seeds suggested by GeNorm were GAPDH, UCP, actin. However, the best combinations of stable genes in each tissue were identified separately under stress conditions: EF1-α, PP2A2 and GAPDH in total stress, however, in SA stress, four genes were required for normalization: PP2A2, EF1-α, GAPDH and PUB. In PEG stress, four genes also were required: PP2A2, EF1-α, GAPDH and PUB, while in NaCl stress, five genes were necessary: PP2A2, GAPDH, EF1-α, PUB and Tβ2. These results are in accordance with two other programs used in this study (NormFinder, BestKeeper). In addition, the transcript levels of Jc-SRG-2 seem to be more correlated with stress responses than changes in transcript levels of Jc-SRG-1, mainly of leaves in exposure to 3-12 h on PEG and NaCl stress. Taken together, GAPDH and PP2A2 were regarded as being the best reference to provide guidelines for the selection of potential references genes under these study conditions.